2020
DOI: 10.1016/j.ijid.2020.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genetic susceptibility to Mycobacterium tuberculosis (VDR and IL10 genes) in a population with a high level of substructure in the Brazilian Amazon region

Abstract: Objectives: Tuberculosis (TB) is an infectious and contagious disease that has been very influential in human history and presents high rates of mortality. The objective of this study was to investigate the association of VDR, IL10, and SLC11A1 gene polymorphisms with susceptibility to the presence of Mycobacterium tuberculosis infection. Methods: A total of 135 patients with confirmed TB and 141 healthy individuals were included in the analysis. Blood samples were collected for DNA extraction. Genotyping of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…However, reports on the genes or SNPs associated with making human beings susceptible to tuberculosis development were inconsistent or contradictory due to the geographical restrictions and ethnic differences. 5 , 25 , 34 There were few reports on the susceptibility genes of tuberculosis in population from Xinjiang, China. 9 , 10 , 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, reports on the genes or SNPs associated with making human beings susceptible to tuberculosis development were inconsistent or contradictory due to the geographical restrictions and ethnic differences. 5 , 25 , 34 There were few reports on the susceptibility genes of tuberculosis in population from Xinjiang, China. 9 , 10 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the distribution frequencies of alleles and genotypes of Fok I, Taq I, Apa I, Bsm I, rs3847987 and rs739837 in patients were not statistically different from that of the control group, which was inconsistent with the previously reported results. 5 , 6 , 39 For example, Sharma et al reported that Bsm I polymorphism appeared associated with the tuberculosis in tribes, castes and Muslims of central India, whereas, Taq I, Fok I and Apa I polymorphisms revealed association in general population and Muslims only. 40 The report in the Brazilian population found that Taq I-TT genotypes, Fok I-CC/(CC+CT) and Bsm I-GG genotypes were significantly associated with tuberculosis susceptibility, of which the homozygotes of Taq I-TT and Bsm I-GG both have approximately twofold increase in risk ratio than other genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that deregulation of miRNAs and miRNA-related genes occur in many diseases ( de Souza et al, 2020 ; Silva et al, 2020 ). DROSHA initiates the biosynthesis of miRNAs by processing pri-miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genetic variants in IL10, VDR, and microRNA genes were reported in subsequent studies in different human populations. However, there were few results of the association between these microRNA polymorphisms and tuberculosis susceptibility ( Song et al, 2013 ; Silva et al, 2020 ). The aim of this study was to perform an association study between SNPs in miRNA and DROSHA and tuberculosis and evaluate whether these selected SNPs may confer susceptibility or protection to TB in the Amazon population.…”
Section: Introductionmentioning
confidence: 99%